ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SEKOLAH MENENGAH MELALUI MODEL CREATIVE PROBLEM SOLVING - Marina Indah Sari; Wisma Eliyarti; Dahlia Fisher (Jurnal Padegogik, 2022)
Using less precise learning models has an impact on students' mathematical problem-solving abilities. Therefore, one of the right models in learning is Creative Problem Solving. Such models can increase the activeness andivity of students in learning. The purpose of this study is to find out how the students' mathematical problem-solving skills through the Creative Problem Solving model. The method used is qualitative research with a type of literature study research. In the literature study using written sources, namely journals, thesis and other relevant written documents. Research is motivated by students' low mathematical problem-solving abilities. The data sources used in this study are primary data and secondary data on mathematical problem solving capabilities, and the Creative Problem Solving model. The results of this study are: students' mathematical problem solving skills using the Creative Problem Solving model have improved well.